Determination of optimal NH4+/K + concentration and corresponding ratio critical for growth of tobacco seedlings in a hydroponic system - Li, Chuanzong; Aluko, Oluwaseun Olayemi; Shi, Sujuan; Mo, Zhijie; Nong, Tongjia; Shi, Chuhan; Li, Zhihao; Wang, Qian; Liu, Haobao (Frontiers in Plant Science, 2023)
Inherently, ammonium (NH4+) is critical for plant growth; however, its toxicity suppresses potassium (K+) uptake and vice-versa. Hence, attaining a nutritional balance between these two ions (NH4+ and K+) becomes imperative for the growth of tobacco seedlings. Therefore, we conducted a 15-day experimental study on tobacco seedlings exposed to different concentrations (47 treatments) of NH4+/K+ at different corresponding 12 ratios simultaneously in a hydroponic system. This experiment. Our study aimed at establishing the optimal NH4+-K+ concentration and the corresponding ratio required for optimal growth of different tobacco plant organs during the seedling stage. The controls were the baseline for comparison in this study. Plants with low or excessive NH4+-K+ concentration had leaf chlorosis or dark greenish colouration, stunted whole plant part biomass, and thin roots. We found that adequate K+ supply is a pragmatic way to mitigate NH4+-induced toxicity in tobacco plants. The optimal growth for tobacco leaf and root was attained at NH4+-K+ concentrations 2-2 mM (ratio 1:1), whereas stem growth was optimal at NH4+-K+ 1-2 mM (1:2). The study provided an insight into the right combination of NH4+/K+ that could mitigate or prevent NH4+ or K+ stress in the tobacco seedlings.